Acquired Constriction Ring: A Case of Rubber Band Syndrome. Issue 6 (June 2019) - Meier, Rahel; Haug, Luzian; Surke, Carsten; Mathys, Lukas; Vögelin, Esther
Abstract : Abstract: Rubber band syndrome is a rare entity seen in younger children mainly in communities where rubber bands are worn around the wrist for decorative purposes. When the band is worn for a long duration, it burrows through the skin and soft tissues resulting in distal edema, loss of function, and even damage to the neurovascular structures. These symptoms are difficult to relate to this rare but typical condition. We report a case of a 2¾-year-old girl with the history of a linear circumferential scar at the right wrist combined with the limited use of a swollen hand for several weeks. The child was taken to surgery with the purpose to release the red, indurated scar and eliminate the lymphatic congestion. A rubber band was found lying in a plane superficial to the flexor tendons but had cut through the superficial branch of the radial nerve and partially through the abductor pollicis longus tendon. The band was removed and the lacerated structures were repaired. The child had excellent recovery postoperatively. The cardinal features of a linear constricting scar around the wrist in the presence of a swollen hand should always alert the clinician to the possibility of a forgotten band around the wrist, which might have burrowed into the soft tissues for a period. Early recognition may be important to prevent further damage of essential structures.